2016
DOI: 10.3847/0067-0049/224/2/17
|View full text |Cite
|
Sign up to set email alerts
|

Infrared and Ultraviolet Spectra of Methane Diluted in Solid Nitrogen and Irradiated With Electrons During Deposition at Various Temperatures

Abstract: We recorded the infrared and ultraviolet absorption spectra of CH4:N2 matrix samples that underwent electron bombardment during deposition in the temperature range of 10–44 K. In contrast to a previous experiment on the IR spectroscopy of electron-bombarded icy samples, methyl and azide radicals became the main products upon electron bombardment during deposition; furthermore, reduced production of nitrile species was observed for deposition at 10 and 20 K. On the other hand, for deposition above 33 K, the obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…In the ISM, solid CH 3 is an intermediate reaction product in the formation of methane. It can also be formed through UV-, electrons-and ions-induced dissociation reactions from ice mixtures containing methane (Milligan & Jacox 1967;Bohn et al 1994;Palumbo et al 2004;Hodyss et al 2011;Kim & Kaiser 2012;Wu et al 2012Wu et al , 2013Materese et al 2014Materese et al , 2015Lo et al 2015;Bossa 2015;Chin et al 2016). The solid CH 4 + OH abstraction reaction investigated here, however, can be an important channel for the formation of methyl radicals under interstellar analog conditions.…”
Section: Astrophysical Implicationsmentioning
confidence: 95%
“…In the ISM, solid CH 3 is an intermediate reaction product in the formation of methane. It can also be formed through UV-, electrons-and ions-induced dissociation reactions from ice mixtures containing methane (Milligan & Jacox 1967;Bohn et al 1994;Palumbo et al 2004;Hodyss et al 2011;Kim & Kaiser 2012;Wu et al 2012Wu et al , 2013Materese et al 2014Materese et al , 2015Lo et al 2015;Bossa 2015;Chin et al 2016). The solid CH 4 + OH abstraction reaction investigated here, however, can be an important channel for the formation of methyl radicals under interstellar analog conditions.…”
Section: Astrophysical Implicationsmentioning
confidence: 95%
“…To engage the photochemical system simply, we intended to eliminate the as-generated l -N 3 at this stage. The vibronic absorption progression of l -N 3 in the icy N 2 was measured by Chin et al in wavelength region 190 to 225 nm (28); therefore, we photolyzed the target icy sample containing the as-generated l -N 3 upon light at 190 nm for 1 h. Also, because the threshold wavelengths of emission of the N α-line and N 2 (A → X) are 145.6 and 175 nm (16), respectively, we used VUV light at 190 nm, which initiates no reaction of N 2 ice, to irradiate the icy N 2 containing as-generated l -N 3 radicals. After we irradiated at 190 nm, we then recorded the IR spectrum of the icy sample shown as spectrum “IR-3” in Fig.…”
Section: Icy N2 Containing As-generated L-n3 Irradiated At 190 Nmmentioning
confidence: 99%
“…The mid-UV reflectance spectra of Pluto and Charon were recorded by the Hubble Space Telescope Cosmic Origins Spectrograph ( HST /COS); Stern et al (30) reported the Pluto’s spectrum contains a strong mid-UV absorption feature. Recently, Chin et al (28) suggested that the carrier of absorption feature of Pluto’s surface observed by HST/COS might be l -N 3 . According to this work, the photochemical process of icy N 2 upon VUV light may possibly produce l -N 3 and N ( 2 D) in the outer Solar System.…”
Section: Implication To Astrosciencementioning
confidence: 99%